Implementasi Fungsi Badan Permusyawaratan Desa dalam Pembangunan Desa Menurut Undang-Undang Nomor 6 Tahun 2014 tentang Desa Di Desa Prambatan Kidul Kecamatan Kaliwungu Kabupaten Kudus - Vedatalitha, Hayyuning Nosa; Madalina, Maria (Res Publica: Jurnal Hukum Kebijakan Publik, 2022)
This article aims to analyze the implementation on function of Village Consultative Body (BPD) in village development in Prambatan Kidul village, Kaliwungu District, Kudus Regency. This research is an empirical legal research or non-doctrinal research with qualitative approach. The type of data used is primary data in form of field data  and secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials. Data collection technique in this research are interviews and literature study. This study uses descriptive qualitative data analysis techniques. The results of this study indicate that the BPD Prambatan Kidul has not been able to function optimally. BPD Prambatan Kidul which has the three main function which are legislative, aspiration and supervision is still lack in collecting the aspirations. Whereas the realization of legislative and supervition has been carried out quite well. In addition, the ability of BPD members to handle aspirations is still not visible. There are inhibiting factors such as the quality of human resources, the facility factor and the Covid-19 virus factor that have a major influence on village development.